Constitutional conditions for combating epidemic diseases in Poland. Selected issues in the light of the experience of counteracting COVID-19 - Bernaciński, Łukasz (The Opole Studies in Administration and Law, 2024)
To counteract the spread of the COVID-19 pandemic, tools interfering with human freedoms and rights were largely used. The new situation related to the epidemic of a previously unknown virus required immediate action, but even in such circumstances public authorities must comply with constitutional provisions. Therefore, the article examines the conditions that the Constitution imposes on the authorities in the field of combating epidemic diseases. The limited framework of the study required the selection of only some issues, and the selection criterion was the controversy related to combating the COVID-19 epidemic in Poland. The final part of the article lists examples of interference with freedoms and human rights that occur during the COVID-19 epidemic, and which have a legal basis in sub-statutory rank laws. Mainly a formal-dogmatic research method was used. The conclusions took the form a kind of recommendation for the actions of public authorities in the period free from the plague.